Patient Safety—Incorporating Drawing Software into Root Cause Analysis Software - Williams, Linda (American Medical Informatics Association, 2002)
Drawing software from Lassalle Technologies1 (France) designed for Visual Basic is the tool we used to standardize the creation, storage, and retrieval of flow diagrams containing information about adverse events and close calls.